Bosnia and Herzegovina : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bosnia and Herzegovina. (IMF Staff Country Reports; Country Report ;, 2021)
Pre-pandemic, Bosnia and Herzegovina's (BiH) economy was growing, but at a pace below the more successful countries in Eastern Europe. The pandemic generated a substantial output contraction in 2020. Early in the pandemic, the authorities successfully implemented restrictions to prevent the spread of the virus and took measures to support firms and households. However, the ongoing second wave poses additional challenges. A gradual recovery is expected for the second half of 2021. Political disagreements about policy coordination at the BiH State level have hampered program implementation under the 2016 EFF arrangement and the deepening of the single economic space. The challenge is to deal with the pandemic and put the economy on a higher medium-term growth trajectory.